Analisis penanaman sikap kerja sama melalui kegiatan ekstrakurikuler pramuka di kelas III sekolah dasar - Zumrotu Ningmah; Siti Istiyati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2024)
This research aims to describe the methods and obstacles to cultivating an attitude of cooperation through Scout extracurriculars in class III A of SDN Panularan No.06 Surakarta for the 2023/2024 academic year. This research uses a descriptive qualitative approach. Data collection techniques through moderate observation, interviews and documentation. Test the validity of the data using triangulation of techniques and sources. Data analysis uses Miles and Huberman analysis techniques. The results of the research show that: (1) The coach has instilled an attitude of cooperation through various means, including the group system succeeded in achieving 5 of the 6 indicators of a cooperative attitude with a percentage of 83% in the very good category, the intervention achieved 3 indicators with a percentage of 50% in the poor category, exemplary and habituation reached 2 indicators with a percentage of 33% in the very poor category due to students forgetting, mentoring and reinforcement reached 2 indicators with a percentage of 33% in the very poor category due to the lack of planning and consequences. The game method and the involvement of various parties reached 2 and 1 indicators respectively with a percentage of 33% and 16.67% in the very poor category, namely only carried out at large meetings (2) Internal obstacles were related to lack of supervision, while external obstacles included limited planning and the number of supervisors. Scout.